Reducing risks to health and wellbeing at mass gatherings: the role of the Sendai Framework for Disaster Risk Reduction. (June 2016) - Aitsi-Selmi, Amina; Murray, Virginia; Heymann, David; McCloskey, Brian; Azhar, Esam I.; Petersen, Eskild; Zumla, Alimuddin; Dar, Osman
Highlights: Reducing the health risks of mass gatherings and seizing the opportunities for health improvement that mass gatherings may offer requires a broader approach to the underlying determinants of risk similar to the comprehensive social determinants of health approach. One of the largest regular mass gatherings in the world is the Hajj. It is the annual mass gathering of over two million Muslims from all over the world and presents challenges to the authorities in Saudi Arabia. The battle against the spread of travel-related infections and other risks facilitated by globalization that arise from mass gatherings is a shared responsibility between different countries, sectors, and disciplines that can help to reduce risk. The Sendai Framework offers a unique opportunity to move beyond simply responding to emergencies to a more comprehensive, prevention-based approach to mass gathering management through the use of science and technical capabilities. It puts the protection of people's health, lives, and livelihoods at its centre. Summary: Mass gatherings of people at religious pilgrimages and sporting events are linked to numerous health hazards, including the transmission of infectious diseases, physical injuries, and an impact on local and global health systems and services. As with other forms of disaster, mass gathering-related disasters are the product of the management of different hazards, levels of exposure, and vulnerability of the population and environment, and require comprehensive risk management that looks beyond single hazards and response. Incorporating an all-hazard, prevention-driven, evidence-based approach that is multisectoral and multidisciplinary is strongly advocated by the Sendai Framework for Disaster Risk Reduction 2015–2030. This paper reviews some of the broader impacts of mass gatherings, the opportunity for concerted action across policy sectors and scientific disciplines offered by the year 2015 (including through the Sendai Framework), and the elements of a 21 st century approach to mass gatherings.